Lay representations on climate change - Cabecinhas, Rosa (2006)
Lay representations on climate change were mapped via the free-word association method in two pilot studies. Participants were asked to generate words associated to “the big problems faced by humankind nowadays” (1st study) and to “climate change” (2nd study). Climate change was not spontaneously evoked by the participants in the first study: pollution was among the top 10 problems, but references to other environmental issues were very low. In the second study, climate change was considered as a threat, and it was associated with diseases, death and destruction. Possible mitigation actions were mentioned by only 4% of the participants, which portrayed themselves as potential victims rather than potential actors of mitigation actions. Results suggest that feelings of risk associated with climate change are not closely related with pro-environment behaviours.